Digital Phenotyping: Ethical Issues, Opportunities, and Threats - Stanghellini, Giovanni; Leoni, Federico (Frontiers in Psychiatry, 2020)
This paper explores the potential threats of digital phenotyping and the ways it may redesign our body experience and conceptualization. We argue that technology in digital medicine, and in psychiatry in particular, is not merely an extrinsic device to achieve improvements in knowledge, diagnosis and treatment of diseases; rather, it intrinsically and unavoidably implies potential effects on what it is to be a human person, namely the embodiment and relatedness in human affairs, and not only in the clinical setting. Last but not least, digital phenotyping may improve prediction of abnormal behaviour but not improve its causal explanation or psychological understanding.